The Strategic Competitional Elements Contributing to Volleyball Performance - Abdullah, Prof. Madya Dr. Mohamad Razali (Springer Science and Business Media Deutschland GmbH, 2021)
This chapter explored the importance of certain psychological strategic elements in the prediction of players performance during the indoor volleyball tournament. It has been demonstrated from the study findings that competitional strategic variables that constituted imagery, self-talk, activation, automaticity as well as emotional control are shown to be pivotal in determining the performance of elite volleyball players during competition. It is then postulated that the ability of an athlete to develop a personal strategy for coping with obstacles will help the athlete produce better results during competition in this sport to a greater extent. © 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.